2015
DOI: 10.1111/jcmm.12388
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial proteomics with siRNA knockdown to reveal ACAT1 and MDH2 in the development of doxorubicin‐resistant uterine cancer

Abstract: Mitochondria are key organelles in mammary cells in responsible for a number of cellular functions including cell survival and energy metabolism. Moreover, mitochondria are one of the major targets under doxorubicin treatment. In this study, low-abundant mitochondrial proteins were enriched for proteomic analysis with the state-of-the-art two-dimensional differential gel electrophoresis (2D-DIGE) and matrix-assistant laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS) strategy to compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 29 publications
3
20
0
3
Order By: Relevance
“… 36 Previous studies also indicated that MDH2 was involved in prostate and uterine cancer chemotherapy resistance. 37 , 38 There was a marked upregulation of MDH2 expression in prostate tumor tissue, and knockdown of MDH2 in prostate cancer cell lines significantly inhibited cell proliferation and increased the sensitivity of docetaxel. 37 A study by Liu et al 37 also observed that overexpression of MDH2 significantly increased the risk of prostate cancer recurrence after receiving neoadjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“… 36 Previous studies also indicated that MDH2 was involved in prostate and uterine cancer chemotherapy resistance. 37 , 38 There was a marked upregulation of MDH2 expression in prostate tumor tissue, and knockdown of MDH2 in prostate cancer cell lines significantly inhibited cell proliferation and increased the sensitivity of docetaxel. 37 A study by Liu et al 37 also observed that overexpression of MDH2 significantly increased the risk of prostate cancer recurrence after receiving neoadjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, AH inhibits cell proliferation of diverse human cancer cells and primary leukemia cells from human patients as well as tumor growth of xenograft nude mice with no obvious off target effect and minimal toxicity. In addition, Lo et al recently suggested that ACAT1 may confer doxorubicin resistance to uterine cancer cells (Lo et al, 2015). These data provide “proof of principle” to suggest targeting tetrameric ACAT1 as a promising therapy in the clinical treatment of human cancer patients with elevated ACAT1 activity and glycolysis rate, as well as relapsed cancer patients with chemo-resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Malate Dehydrogenase (MDH) MDH2 produces oxaloacetate from malate and has also been detected in cancer cell nuclei, but its non-canonical function is unknown [58,63]. MDH1, the cytoplasmic isoenzyme, translocates in the nucleus under low-glucose conditions, promoting p53-mediated cell-cycle arrest and apoptosis [58,64].…”
Section: Fumarasementioning
confidence: 99%